Analisis Laporan Keuangan sebagai dasar dalam Penilaian Kinerja Keuangan PT. Budi Satria Wahana Motor - Riswan RISWAN; Yolanda Fatrecia Kesuma (Universitas Bandar Lampung (UBL), 2014)
AbstractThis research aims to analyze the financial performance of PT BUDI SATRIA MOTOR VEHICLE in terms of the ratio of solvency, liquidity, profitability and activity ratios in 2009 until 2012.This study uses data collected in 2009-2012 for financial data company. The Data used in this study is secondary data, where writers get data indirectly through intermediaries and media studies libraryPenelitian ini Based on the results of the research, it can be concluded that the companys financial performance has not been good. In terms of liquidity ratio, whereby cash and banks havent been able to guarantee the debt. Review of the solvency ratio, the large amount of debt is not comparable to that of its own capital. On the ratio of profitability, where this ratio tends to decrease. And on the ratio of the activity, the company has showed an increase. From the research, that suggested company to pt.Budi satria the motor had to do the analysis ratio to know further about condition or circumstances of corporate finance.